Dyscalculia and dyslexia in school-aged children: comorbidity, support, and future prospects - Han, Weifeng (Frontiers in Education, 2025)
The comorbidity of dyscalculia and dyslexia represents a significant challenge in education, affecting a considerable number of school-aged children globally. This Mini Review synthesizes literature from the last decade (2015–2024) to provide an updated perspective on the prevalence, etiology, and educational implications of these co-occurring learning differences. Despite recent advancements in screening, diagnostic, and intervention tools, significant gaps remain in addressing the unique needs of children facing both dyscalculia and dyslexia. This review highlights the limitations of current research, particularly the scarcity of studies focused on culturally and linguistically diverse (CALD) populations and socio-economic disparities and explores the urgent need for more comprehensive, integrated approaches. Future directions include leveraging technological innovations, fostering interdisciplinary collaborations, and adopting neurodiversity-based educational models to support affected learners effectively. Addressing these gaps can foster an inclusive learning environment and improve outcomes for children navigating the complexities of both dyscalculia and dyslexia.